2020
DOI: 10.1063/1.5130748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interstitial carbon on the evolution of early-stage irradiation damage in equi-atomic FeMnNiCoCr high-entropy alloys

Abstract: Owing to their excellent radiation tolerance, some of the high-entropy alloys (HEAs) are considered as potential candidates for structural materials in extreme conditions. In order to shed light on the early-stage irradiation damage in HEAs, we performed positron annihilation spectroscopy on hydrogen implanted equi-atomic FeMnNiCoCr and interstitial carbon-containing FeMnNiCoCr HEAs. We reveal primary damage as mono-vacancies in low dose irradiated HEAs. The enhancement of Frenkel pair recombination by C addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Experimentally, the formation of Cu-V complexes and vacancy-like defects surrounded by tiny Cu precipitates in Fe-Cu model alloys was detected by slow positron spectroscopy. In the previous study of hydrogen irradiated metal, also an effect of the alloying elements on the irradiated-induced defects was observed [19,20]. Also recent work on the hydrogen implanted C-containing FeMnNiCoCr high-entropy alloys demonstrated that the interaction between the interstitial C atoms and irradiated-induced vacancies will inhibit the aggregation of vacancy clusters [19].…”
Section: Introductionmentioning
confidence: 95%
“…Experimentally, the formation of Cu-V complexes and vacancy-like defects surrounded by tiny Cu precipitates in Fe-Cu model alloys was detected by slow positron spectroscopy. In the previous study of hydrogen irradiated metal, also an effect of the alloying elements on the irradiated-induced defects was observed [19,20]. Also recent work on the hydrogen implanted C-containing FeMnNiCoCr high-entropy alloys demonstrated that the interaction between the interstitial C atoms and irradiated-induced vacancies will inhibit the aggregation of vacancy clusters [19].…”
Section: Introductionmentioning
confidence: 95%
“…Positron annihilation experiments in hydrogen implanted equimolar FeMnNiCoCr with varying concentrations of C interstitials suggest that C effectively reduces the radiation damage by enhancing Frenkel pair recombination and suppressing vacancy clustering. [ 84 ] In contrast, removal of self‐irradiation damage (Ni ions) appears to require relatively high temperature treatments in the four‐component alloys. [ 89 ] Further work is expected to elucidate the point‐defect related phenomena in a wide variety of high‐entropy alloys.…”
Section: High‐entropy Alloysmentioning
confidence: 99%
“…The focus has been on the early stages of radiation damage formation, as one of the great promises of this class of materials is increased radiation tolerance compared with traditional alloys. [82][83][84][85][86] Studies on the thermal formation of vacancies in high-entropy alloys are also emerging. [87,88] Interpretation of positron annihilation results in high-entropy alloys faces similar challenges as in the nitride semiconductor alloys discussed earlier, but to a higher degree as the distribution of atoms surrounding a vacancy contains more elements.…”
Section: High-entropy Alloysmentioning
confidence: 99%
“…However, related research is rare to date. Lu et al [ 12 ] observed monovacancies in FeMnNiCoCr HEA using positron annihilation spectroscopy (PAS) after irradiation with low doses of hydrogen. Ramachandran et al [ 13 ] applied PAS to investigate the evolution of defects with temperature in RAFM steel irradiated by hydrogen and helium.…”
Section: Introductionmentioning
confidence: 99%